Design of Diabetes Mellitus Monitoring System (SIMON-DM) Using Rapid Application Development (RAD) Method: Case Study of Manonjaya Health Center - Fadillah Awaliyah Ramdhani; Fery Fadly (Poltekkes Kemenkes Tasikmalaya, 2026)
Background: Diabetes mellitus is a degenerative disease that continues to increase in Indonesia and is one of the main causes of health complications. Inconsistent monitoring is a challenge in the management of this disease, especially in primary health care facilities such as community health centers. This study aims to design a technology-based diabetes mellitus monitoring system with a Rapid Application Development (RAD) approach to improve the efficiency of monitoring patient conditions. Method: This study uses the Rapid Application Development (RAD) method which consists of 4 stages, namely needs planning, system design, development and system implementation. Data were obtained through interview techniques, observation and documentation at the Manonjaya Community Health Center from five informants from various groups such as doctors, health workers and patients. Data analysis used triangulation of sources and techniques to ensure that the data was truly relevant. Results: The result of this study is a diabetes mellitus monitoring system named SIMON-DM (Sistem Monitoring Diabetes Mellitus). System testing conducted on four respondents showed that the system obtained an average feasibility score of 3.6 out of 4, indicating that SIMON-DM is categorized as good to very good and suitable for implementation in primary healthcare settings.. Conclusion: The diabetes mellitus monitoring system developed is in accordance with user needs and is able to support independent and integrated disease management in health care facilities.